The Palaeoproterozoic Warramunga Formation, Tennant Creek Block, Central Australia: Sedimentology, Geochemistry and Provenance - N Donnellan (The Australasian Institute of Mining and Metallurgy, 1994)
The Palaeoproterozoic Warramunga Formation is notable as the host to the enigmatic, so-called 'Tennant Creek style' mineralisation. These polymetallic (but mainly Au-Cu-Bi) ore deposits typically have a close spatial association with massive ironstone bodies, and frequently also with banded ironstone, known locally as 'haematite shale'. The Warramunga Formation is a polydeformed, turbiditic succession. Partial, or complete Bouma sequences variously comprising lithic arenite, wacke, siltstone, and mudstone constitute a classic flysch sequence deposited as a proximal (sandstone lithofacies) to distal (siltstone lithofacies) fan association. The Warramunga Formation has a substantial component of volcanic detritus and has generally been attributed to an essentially contemporaneous volcanic provenance. However, lithostratigraphic revision (Donnellan, Hussey and Morrison, in press) apparently precludes outcropping volcanic rocks of the Tennant Creek Block, or indeed Inlier, as the source of detritus. Warramunga Formation geochemistry indicates rapid derivation from a fractionated, predominately felsic igneous source (Palaeoproterozoic upper crust) with a minimum of chemical weathering; together with an admixture of mafic material. Warramunga Formation geochemistry cannot, however, be reconciled with that of the Bemborough Formation, which is here taken to be representative of Flynn Subgroup felsic volcanic rocks. Similarly, the Warramunga Formation is geochemically distinct from Flynn Subgroup sedimentary rocks. Geochemistry of the banded ironstone is consistent with its interpretation as Dine-grained turbidites.